The incidence of bradyarrhythmias and clinical bradyarrhythmic events in patients with acute coronary syndromes treated with ticagrelor or clopidogrel in the PLATO (Platelet inhibition and patient outcomes) trial: results of the continuous electrocardiographic assessment substudy - Scirica, Benjamin M.; Cannon, Christopher P.; Emanuelsson, Håkan; Michelson, Eric L.; Harrington, Robert A.; Husted, Steen; James, Stefan; Katus, Hugo; Pais, Prem; Raev, Dimitar; Spinar, Jindrich; Steg, Ph. Gabriel; et al. (Journal of the American College of Cardiology, 2011)
Objectives - The aim of this study was to determine whether ticagrelor increased the risk of ventricular pauses compared with clopidogrel and whether these pauses were associated with any clinical bradycardic events in patients presenting with acute coronary syndromes. - Background - Ticagrelor, an oral reversibly binding P2Y12 inhibitor, provides more potent and consistent inhibition of platelet aggregation than clopidogrel but in a phase II study was associated with increased risk for ventricular pauses. A prospective continuous electrocardiographic (cECG) assessment was therefore performed within the PLATO (Platelet Inhibition and Patient Outcomes) study comparing ticagrelor and clopidogrel in patients hospitalized with acute coronary syndromes. - Methods - Patients in the cECG assessment had planned 7-day cECG recording initiated at the time of randomization (week 1), which was within 24 h of symptom onset, and then repeated at 1 month after randomization during the convalescent phase. The principal safety endpoint was the incidence of ventricular pauses lasting at least 3 s. Investigators also reported symptomatic bradycardic adverse events during the entire study duration (median 277 days). - Results - A total of 2,908 patients were included in the cECG assessment, of whom 2,866 (98.5%) had week 1 recordings, 1,991 (68.4%) had 1-month recordings, and 1,949 (67.0%) had both. During the first week after randomization, ventricular pauses ≥3 s occurred more frequently in patients receiving ticagrelor than clopidogrel (84 [5.8%] vs. 51 [3.6%]; relative risk: 1.61; p = 0.006). At 1 month, pauses ≥3 s occurred overall less frequently and were similar between treatments (2.1% vs. 1.7%). Most were ventricular pauses, and the greatest excess associated with ticagrelor were asymptomatic, sinoatrial nodal in origin (66%), and nocturnal. There were no differences between ticagrelor and clopidogrel in the incidence of clinically reported bradycardic adverse events, including syncope, pacemaker placement, and cardiac arrest. - Conclusions - In the PLATO cECG assessment, more patients treated with ticagrelor compared with clopidogrel had ventricular pauses, which were predominantly asymptomatic, sinoatrial nodal in origin, and nocturnal and occurred most frequently in the acute phase of acute coronary syndromes. There were no apparent clinical consequences related to the excess in ventricular pauses in patients assigned to ticagrelor. (A Comparison of AZD6140 and Clopidogrel in Patients With Acute Coronary Syndrome [PLATO]; NCT00391872)